Continuous or intermittent feeding: pros and cons. Issue 4 (August 2018) - Bear, Danielle E.; Hart, Nicholas; Puthucheary, Zudin
Abstract : Purpose of review: There has been a recent shift in the focus of providing nutrition support to critically ill adults towards enhancing recovery and promoting survivorship. With this has come an evaluation of our current approaches to nutrition support, which includes whether continuous feeding is optimal, particularly for reducing muscle wasting, but also for managing blood glucose levels and feeding intolerance and at the organizational level. This review will discuss the pros and cons of using intermittent and continuous feeding relating to several aspects of the management of critically ill adults. Recent findings: Few studies have investigated the effect of intermittent feeding over continuous feeding. Overall, intermittent feeding has not been shown to increase glucose variability or gastrointestinal intolerance, two of the reasons continuous feeding is the preferred method. A current study investigating the effect of intermittent vs. continuous feeding is awaited to provide insight into the effect of muscle wasting. Summary: Although there are limited studies investigating the safety and efficacy of an intermittent rather than continuous feeding regimen in critically ill adults, there are several theoretical advantages. Further studies should investigate these and in the meantime, feeding regimens should be devised based on individual patient factors.